Membangun Rantai Pembelian Ulang Wisatawan - Yudi Setiaji (Media Wisata, 2012)
Satisfaction and rebuying become the key factor influencing the advantage and growth of tourism companies in a long term. This research test the model of the relation of quality perception, satisfaction, and rebuying tourist market which a mediated by trust.The questioner was used to collect the data from 300 respondents, test the validity and reliability confirmation with the coefficient of Cronbach alpha. Analyse the data to test the hypothesis this research used a structural equation model healthily to collect the data. The result of the empirical study indicates that a whole found a causality relation at four accurate a company, satisfaction directly influenced by the perception of quality and rebuying mediated by trust of a customer to the company.This research implication indicates that the company owning higher level tourist satisfaction storey; level will be easier to customer becomes the devoted to doing the rebuying, therefore strengthen the ability and improve its speciality go together with the customer service, will make the company do not only limited to able to hold out attacked from serangan competitor but also able to grow healthily industrial market service which hyper-competition.